The effect of calcium carbonate and calcined clay micro filler materials on the electrical characteristics of polyvinyl chloride for cable insultion [Electronic Resource] - 381435 Mohd. Asyraf Reduan Azmi (2008)
Thesis (Sarjana Kejuruteraan (Kuasa Eletrik)) - Universiti Teknologi Malaysia, 2008